2006
DOI: 10.1210/en.2006-0615
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone-II Messenger Ribonucleic Acid and Protein Content in the Mammalian Brain Are Modulated by Food Intake

Abstract: GnRH-II is the most evolutionarily conserved member of the GnRH peptide family. In mammals, GnRH-II has been shown to regulate reproductive and feeding behaviors. In female musk shrews, GnRH-II treatment increases mating behaviors and decreases food intake. Although GnRH-II-containing neurons are known to reside in the midbrain, the neural sites of GnRH-II action are undetermined, as is the degree to which GnRH-II is regulated by energy availability. To determine whether GnRH-II function is affected by changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…decline of circulating LH and testosterone, however can be reversed rapidly upon feeding, suggesting that there is a calorie-dependent regulation of GnRH pulse-generator output (Aloi et al, 1997). Further linking GnRH function, there is evidence of not only GnRHs role in generic neuronal excitability during fasting (Röjdmark, 1987), controlling the desire behind food intake (Kauffman et al, 2005a), but there is also evidence that food intake itself directly controls the mRNA and protein levels of GnRH in mammalian brains (Kauffman et al, 2006). It has been shown that even short periods of dietary energy deprivation (24-72 h) can have dramatic effects upon the hypothalamic-pituitary-gonadal (HPG) axis in humans and animal models.…”
Section: Ghrelin and Growth Hormonementioning
confidence: 99%
“…decline of circulating LH and testosterone, however can be reversed rapidly upon feeding, suggesting that there is a calorie-dependent regulation of GnRH pulse-generator output (Aloi et al, 1997). Further linking GnRH function, there is evidence of not only GnRHs role in generic neuronal excitability during fasting (Röjdmark, 1987), controlling the desire behind food intake (Kauffman et al, 2005a), but there is also evidence that food intake itself directly controls the mRNA and protein levels of GnRH in mammalian brains (Kauffman et al, 2006). It has been shown that even short periods of dietary energy deprivation (24-72 h) can have dramatic effects upon the hypothalamic-pituitary-gonadal (HPG) axis in humans and animal models.…”
Section: Ghrelin and Growth Hormonementioning
confidence: 99%
“…The third GnRH II-related area we examined, the mHB, was non-responsive to food condition and this region also has little or no NPY-ir in the rat (de Quidt and Emson, 1986). GnRH II mRNA and peptide content are likewise affected by energy status, both decrease after 2 days of food restriction (the same feeding paradigm used here) and GnRH II mRNA was reversed by 90 minutes of ad libitum access to food (Kauffman, Bojkowska, Wills, and Rissman, 2006). GnRH II content in the PAG showed the inverse response to restriction and refeeding as compared with NPY-ir; GnRH II peptide levels dropped in restricted females and increased after 180 minutes (but not sooner) of food intake.…”
Section: Discussionmentioning
confidence: 93%
“…In musk shrews, both GnRH I and GnRH II fibers are present in the hypothalamus. Protein and mRNA levels of both peptides are affected by food intake (Kauffman et al, 2006;Temple and Rissman, 2000a). The amount of GnRH I peptide in the median eminence is reduced by food restriction and this affects ovulation (Temple and Rissman, 2000a), and GnRH II reduces food intake and is permissive for reproduction (Temple et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, ICV infusion of cGnRH-II but not mGnRH stimulated sexual behavior in nutritionally challenged female musk shrews (Temple et al, 2003). When musk shrews were exposed to different levels of caloric intake, cGnRH-II mRNA expression was modulated by feed intake (Kauffman et al, 2006;Kauffman and Rissman, 2004b). These data suggest a role of GnRH-II in both feeding and sexual behavior.…”
Section: Chicken Gnrh-iimentioning
confidence: 87%